2017
DOI: 10.1111/psyp.12989
|View full text |Cite
|
Sign up to set email alerts
|

Startle reflex modulation during threat of shock and “threat” of reward

Abstract: During threat of shock, the startle reflex is potentiated, suggesting modulation by defensive mobilization. To determine whether startle potentiation is specific to aversive anticipation, startle reflexes were measured in the context of either aversive or appetitive anticipation in a between-subject study. Participants wore a device on the wrist that could deliver electrical shock (n = 49), or vibrotactile stimulation indicating monetary reward (n = 48). Cues signaling "threat" or "safe" periods were presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…It has been suggested that, during US anticipation in conditioning tasks, general arousal contributes to startle magnitude (Dichter, Tomarken, & Baucom, ; Sabatinelli, Bradley, & Lang, ). This notion is supported by the finding that startle potentiation also occurs in anticipation of pleasant US in appetitive conditioning (Bradley, Zlatar, & Lang, ; Mallan & Lipp, ; Mallan, Lipp, & Libera, ), whereas the startle reflex should be inhibited if it was valence modulated (as it is during positive affective picture viewing; Bradley et al, ; Hamm et al, ). Hence, both arousal during US anticipation as well as an acquired negative valence of the CS+ may contribute to the stimulus discrimination captured by the startle reflex.…”
Section: Discussionmentioning
confidence: 85%
“…It has been suggested that, during US anticipation in conditioning tasks, general arousal contributes to startle magnitude (Dichter, Tomarken, & Baucom, ; Sabatinelli, Bradley, & Lang, ). This notion is supported by the finding that startle potentiation also occurs in anticipation of pleasant US in appetitive conditioning (Bradley, Zlatar, & Lang, ; Mallan & Lipp, ; Mallan, Lipp, & Libera, ), whereas the startle reflex should be inhibited if it was valence modulated (as it is during positive affective picture viewing; Bradley et al, ; Hamm et al, ). Hence, both arousal during US anticipation as well as an acquired negative valence of the CS+ may contribute to the stimulus discrimination captured by the startle reflex.…”
Section: Discussionmentioning
confidence: 85%
“…However, participants appeared to learn that they were in fact safe of shocks in so-called threat blocks when the experiment was of a long duration 20 . A third possibility is to add monetary stimulation in safe blocks, which causes stimulation and makes these blocks 'appetitive' rather than neutral 14,65 . Nevertheless, these 3 methods still do not appear to be fully appropriate to specifically investigate long-lasting anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is mixed evidence that the ERN is directly related to such physiological measures during error commission (Hajcak, McDonald, & Simons, 2003a;Lewis & Pitts, 2015;Lo, Schroder, Moran, Durbin, & Moser, 2015;Moser, Moran, Schroder, Donnellan, & Yeung, 2014;Riesel, Weinberg, Moran, & Hajcak, 2013), raising questions as to whether motivational influences on ERN magnitude reflect increased motivational significance in relation to a specific error, or more general increases in motivation that result in enhanced ERN magnitude. Indeed, measures such as skin conductance and startle potentiation are highly sensitive to contextual factors that increase motivation and arousal (Bradley et al, 2018;Grillon, 2002). Thus, it is possible that contextual influences on the ERN in part represent more general motivational factors unrelated to error commission.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, other psychophysiological measures of motivation, such as startle potentiation, pupil dilation, and skin conductance, are also increased following error commission (Critchley, Tang, Glaser, Butterworth, & Dolan, ; Hajcak & Foti, ; Hajcak, McDonald, & Simons, ; Riesel et al, ). Critically, these psychophysiological measures are also sensitive to contextual factors (Bradley, Zlatar, & Lang, ; Chiew & Braver, ), further emphasizing the role of motivation in influencing ERN magnitude.…”
Section: Introductionmentioning
confidence: 99%